2018
DOI: 10.5194/aab-61-505-2018
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphism in melatonin receptor 1A and arylalkylamine N-acetyltransferase and its impact on seasonal reproduction in Egyptian sheep breeds

Abstract: This study was carried out to detect polymorphisms in the melatonin receptor 1A (MTNR1A) and arylalkylamine N-acetyltransferase (AA-NAT) genes and their association with reproductive traits. Blood samples of 126 animals from three Egyptian sheep breeds were collected. DNA was extracted and subjected to PCR restriction fragment length polymorphism (RFLP) analysis using the RsaI and SmaI enzymes. Two alleles (C and T) and three genotypes (CC, CT and TT) for MTNR1A and for AA-NAT (A and G; GG, GA and AA) were det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 38 publications
2
13
0
Order By: Relevance
“…The frequency of the mutant allele G at position g.17355452 G>A of the MTNR1A gene exon II sequence in our study was similar to those found in other sheep breeds [16,[29][30]. Our results, moreover, showed that at the position g.17355458 C>T, the frequency of the T allele was higher than it is in the Sarda breed, but very similar to those in some Indian and Egyptian sheep breeds [31][32][33].…”
Section: Discussionsupporting
confidence: 89%
“…The frequency of the mutant allele G at position g.17355452 G>A of the MTNR1A gene exon II sequence in our study was similar to those found in other sheep breeds [16,[29][30]. Our results, moreover, showed that at the position g.17355458 C>T, the frequency of the T allele was higher than it is in the Sarda breed, but very similar to those in some Indian and Egyptian sheep breeds [31][32][33].…”
Section: Discussionsupporting
confidence: 89%
“… 7 , 21 Ewes’ seasonal reproductive activity is linked to the presence of many polymorphic sites at the MTNR1A locus, which can be found to be variable. 5 , 22 Despite the fact that the ramifications of the MTNR1A gene on reproductive seasonality have only been investigated to a limited extent up until this point, those studies have shown that these effects are tied to three specific mutations discovered in exon II at locations 606, 612, and 706, 7 , 21 only sheep of the Sarda and Aragonese breeds have had the remaining portions of this gene examined. 12 , 13 , 23 25 …”
Section: Mtnr1a Locationmentioning
confidence: 99%
“…It has been noted that in sheep breeds where estrous activity peaks during short days, variations in day length may function as a main factor determining seasonal variations in estrous activity. 5 7 In the pineal gland, the indole hormone melatonin (MT) is produced, 8 which is linked to changes in light signals of the external natural environment. 9 13 …”
Section: Introductionmentioning
confidence: 99%
“…The relationship between melatonin receptors polymorphism and female fertility has been proven (32,(39)(40)(41). There are also numerous reports suggesting a protective effect of melatonin administration on fertility, maintenance of pregnancy and prevention of birth defects in females exposed to cytostatics, insecticides, herbicides and alcohol (42-46), which is directly related to its antioxidant nature.…”
Section: In Vivo Animal Studiesmentioning
confidence: 99%